Mutu Pendidikan Islam di Tengah Globalisasi: Tinjauan Manajerial dan Strategi Penguatan - Teguh Karya; Anis Zohriah; Agus Gunawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Globalization has had a significant impacton the development of Islamic education, particularly in terms of its quality and competitiveness. This paper aims to analyze the quality of Islamic education from a managerial perspective and formulate appropriate strengthening strategies to address global challenges. The method applied is a literature review of various sources on Islamic education, educational management, and global policies. The research findings indicate that the main challenges lie in institutional aspects, human resource quality, and curriculum relevance. Quality improvement strategies include management reform based on Total Quality Management (TQM), enhancing educators' capabilities, leveraging digital technology, and strengthening partnership networks. Conversely, quality disparities between regions pose an urgent issue of educational equity. Through well-planned and values-based strategies, Islamic education can function as a transformative force that is not only relevant at the global level but also deeply rooted in Islamic values.